Contribution of different sources to the pollution of wet weather flows in combined sewers - Gromaire, M.C.; Garnaud, S.; Saad, M.; Chebbo, G. (Water Research, 2001)
Experiments performed on ‘‘Marais’’ catchment, in central Paris, aimed to follow up the duality of wet weather Rows from the entry to the exit of a combined sewer network. SS, VSS, GOD, BOD5, Cd, Cu, Pb, Zn concentrations were measured for an important number of rain events in roof, yard, street runoff, as well as in dry and wet weather flows at the catchment outlet. Mass entry-exit totals, at the scale of the catchment, were calculated over 31 rain events in order to evaluate the contribution of different types of runoff, of sanitary sewage and of sewer sediments to the total wet weather pollutant loads at the catchment outlet. The erosion of in-sewer pollutant stocks was found to be the main source of particles and of organic matter in wet weather flows, whereas heavy metal loads mainly originated from roof runoff due to the corrosion of metallic roofs. Particles eroded inside the sewer during rain events were found to be quite different from the particles constituting the main part of sewer sediments: they are organic and biodegradable, with rather important settling velocities and seem to accumulate during dry weather periods. A change of the chemical form of heavy metals was noticed during the transport in the sewer and it is suspected that a fraction of the dissolved metals from the runoff is adsorbed on sewer sediments. (C) 2000 Elsevier Science Ltd. All rights reserved